2016
DOI: 10.1186/s12885-016-2561-1
|View full text |Cite
|
Sign up to set email alerts
|

POSITIVE study: physical exercise program in non-operable lung cancer patients undergoing palliative treatment

Abstract: BackgroundPatients with advanced stage non-small cell lung cancer (NSCLC) or small cell lung cancer (SCLC) often experience multidimensional impairments, affecting quality of life during their course of disease. In lung cancer patients with operable disease, several studies have shown that exercise has a positive impact on quality of life and physical functioning. There is limited evidence regarding efficacy for advanced lung cancer patients undergoing palliative treatment. Therefore, the POSITIVE study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 70 publications
0
19
0
4
Order By: Relevance
“…Related to active living and physical exercise is the concept of physical fitness, a well-known and powerful health marker [ 18 , 19 , 20 ] among middle-aged populations, it is even more powerful than physical activity [ 7 ] but we must understand physical fitness as a concept broader than one related exclusively to biological health; it can be defined as the ability to carry out daily tasks with vigor and liveliness, without excessive fatigue, and with enough energy remaining to enjoy leisure time or to cope with unexpected emergencies [ 21 ]. Therefore, in addition to being related to biological health, physical fitness is also closely related to psychosocial factors on the human spectrum and has been found to influence fitness parameters [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related to active living and physical exercise is the concept of physical fitness, a well-known and powerful health marker [ 18 , 19 , 20 ] among middle-aged populations, it is even more powerful than physical activity [ 7 ] but we must understand physical fitness as a concept broader than one related exclusively to biological health; it can be defined as the ability to carry out daily tasks with vigor and liveliness, without excessive fatigue, and with enough energy remaining to enjoy leisure time or to cope with unexpected emergencies [ 21 ]. Therefore, in addition to being related to biological health, physical fitness is also closely related to psychosocial factors on the human spectrum and has been found to influence fitness parameters [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few adequately powered RCTs are published to date examining exercise for patients undergoing non-surgical treatments, although several trials are nearing completion internationally. 45,46 For patients with advanced lung cancer, a Cochrane review of exercise training, which included six RCTs, reported significant improvements in exercise capacity and disease-specific HRQoL favouring the intervention group but no differences in dyspnoea, mood or respiratory function. 47 Included studies were rated as low quality.…”
Section: During and Following Non-surgical Treatmentmentioning
confidence: 99%
“…In addition, pre-operative exercise training was associated with improved lung function recovery after surgery and reduced post-operative pulmonary complications (51,73). In a study by Licker et al that investigated the effectiveness of preoperative exercise training on postoperative outcomes in people undergoing lung resection for NSCLC, independent predictors of postoperative pulmonary complications were preoperative peakVO2, pre-operative exercise training, and COPD [56,57].…”
Section: The Role Of Exercise Training/therapymentioning
confidence: 99%
“…In patients with advanced lung cancer exercise training programmes should aim to prevent deterioration in important clinical outcomes, control symptoms and maximise independence. This is an area of growing interest amongst researchers and clinicians, and there are several RCTs being conducted to investigate effectiveness of exercise training in this population [56][57][58]. To date, exercise training has been shown to be feasible and safe in patients with advanced lung cancer [59].…”
Section: The Role Of Exercise Training/therapymentioning
confidence: 99%